2003
DOI: 10.1034/j.1600-0463.2003.11101031.x
|View full text |Cite
|
Sign up to set email alerts
|

Association between testicular dysgenesis syndrome (TDS) and testicular neoplasia: Evidence from 20 adult patients with signs of maldevelopment of the testis

Abstract: Based on a well established association between testicular cancer and undescended testis and more recent publications on epidemiological links between these disorders and male infertility, we proposed the existence of a testicular dysgenesis syndrome (TDS). In most cases TDS presents with impaired spermatogenesis, only in rare cases the full range of its signs, including genital malformations and testicular cancer can be seen in one patient. In order to further corroborate our hypothesis about the presence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
85
0
4

Year Published

2005
2005
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(90 citation statements)
references
References 42 publications
1
85
0
4
Order By: Relevance
“…They provided evidence for a TGCT predisposition locus on chromosome Xq27 (TGCT1); however, this putative gene has yet to be identified and probably other TGCT putative genes exist. Recently, other suggestions of a genetic basis for TC (Chemes et al 2003, Skakkebaek et al 2003 have been made; however, specific genetic alterations including genetic susceptibility to endocrine disruption are still unknown. Although definitive proof is still lacking, it is generally assumed that the development of TC is under endocrine control (Rajpert-De Meyts et al 1993).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They provided evidence for a TGCT predisposition locus on chromosome Xq27 (TGCT1); however, this putative gene has yet to be identified and probably other TGCT putative genes exist. Recently, other suggestions of a genetic basis for TC (Chemes et al 2003, Skakkebaek et al 2003 have been made; however, specific genetic alterations including genetic susceptibility to endocrine disruption are still unknown. Although definitive proof is still lacking, it is generally assumed that the development of TC is under endocrine control (Rajpert-De Meyts et al 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Increasing adverse factors in male reproductive health as reduced sperm quality, TC, undescended testis and hypospadias might be symptoms of one underlying entity named testicular dysgenesis syndrome (TDS) (Møller & Skakkebaek 1999, Skakkebaek et al 2001, Aitken & Sawyer 2003, Bolsen et al 2004. The aetiology of TDS is supposed to be related either to environmental factors, so-called endocrine disrupters (Weir et al 2000, Huyge et al 2004, and chemical toxicants (Toppari & Skakkebaek 1998, Guo et al 2000 or to genetic factors (Rapley et al 2000, Hemminki & Li 2004, including genetic susceptibility to endocrine disruption (Skakkebaek et al 2003). TDS is supposed to arise during early foetal development when male reproductive tract formation, germ cell proliferation and Sertoli and Leydig cell differentiation occur (Yasuda et al 1985, Sharpe & Skakkebaek 1993, Skakkebaek et al 2001.…”
Section: Introductionmentioning
confidence: 99%
“…[37][38][39][40][41][42] 43 have shown a strong correlation between the presence of the Y chromosome and the severity of the gonadal dysgenesis. Gonadoblastoma acts as an 'in situ' precursor in these patients.…”
Section: Pathogenesismentioning
confidence: 99%
“…Gonadoblastoma acts as an 'in situ' precursor in these patients. Recently, Skakkebaek and co-workers 37,42 suggested that many patients with testicular GCT have some evidence of gonadal dysgenesis in the contralateral gonad, be it microlithiasis, Sertoli-cell-only tubules, seminiferous tubules with undifferentiated Sertoli cells or IGCNU. If this is true, it suggests that a specific genetic mutation may not be required to initiate the process of tumor development, but rather environmental factors are sufficient as initiating events.…”
Section: Pathogenesismentioning
confidence: 99%
“…Subsequent research demonstrated a coordinated, dosedependent reduction in expression of key genes and proteins involved in cholesterol transport and steroidogenesis and a corresponding reduction in testosterone in the fetal testes (Lehmann et al, 2004). In humans, similar dysgenetic changes in the histology of the testis have been found in patients with testicular cancer, subfertility, or cryptorchidism (Sohval, 1954(Sohval, , 1956Berthelsen & Skakkebaek, 1983;Hoei-Hansen et al, 2003;Skakkebaek et al, 2003). Furthermore, men with rare genetic abnormalities that cause testicular dysgenesis (e.g.…”
Section: ) Phthalatesmentioning
confidence: 88%